Mathematics Anxiety and Competence: Exploring Links - Hurst, Chris; Cooke, Audrey (Research and Training Institute of East Aegean, 2012)
Mathematical competence of pre-service teachers is of concern for teacher educators in Australia. Similarly, high levels of anxiety about mathematics in general and low levels of confidence about working with mathematics are disconcerting. This paper reports on a project that investigates links between mathematical competence, conceptual understanding and confidence in pre-service teachers. Three questionnaires designed to measure pre-service teacher attitudes about mathematics in different contexts - working with others, taking a mathematics test, and having to teach mathematics - were administered. Pre-service teachers were also asked to sit an on-line mathematics competency test and were given an opportunity to complete a follow-up questionnaire a year later. Statements on the initial questionnaires represented four domains- somatic, cognitive, attitudinal, and mathematical knowledge. Data generated from participants' reported concerns about mathematics suggest that first year pre-service teachers are most concerned about their levels of knowledge and mathematical understanding and that these concerns are particularly evident when they are required to work with others on mathematics or think about having to teach mathematics. Their levels of anxiety can be somewhat lessened by targeted professional learning using a constructivist approach to developing conceptual understanding. Finally, it was found that responses to the three questionnaires could be used to partially predict attainment on a mathematics competency test.Mathematics education, attitudes, competency, pre-service teachers